The Geological and sociological factors influencing the construction and occupation of historic stone mining shelters, Bahia State, Brazil, 1844 – present - Funch, Roy Richard (Brazilian Journal of Science, 2022)
The geological and sociological factors that influenced the construction and habitation of the “toca” rockshelters built and occupied by diamond miners starting in 1844 are discussed. Extensive field excursions were made into the Chapada Diamantina Mountains, in what is now the Chapada Diamantina National Park, over a period of more than 40 years to document the archaeological vestiges of the diamond rush there. A total of 650 archaeological features were identified, geo-referenced, photo-documented, and classified; 286 of those features were “toca” rockshelters and 53 were stone houses. The local geology, water resources, regional climate, and human factors dictated the construction and occupation of those shelters, including the availability of appropriate overhanging rock ledges, the proximity of potable water, site humidity, and the proximity of diamond-bearing formations. The “toca” shelters themselves share a number of common features, including fire pits, a lack of windows, construction without the use of mortar, and the avoidance of East-facing sites.